The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.psj.2020.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Dietary betaine improves egg-laying rate in hens through hypomethylation and glucocorticoid receptor–mediated activation of hepatic lipogenesis-related genes

Abstract: In avian species, liver lipid metabolism plays an important role in egg laying performance. Previous studies indicate that betaine supplementation in laying hens improves egg production. However, it remains unclear if betaine improves laying performance by affecting hepatic lipid metabolism and what mechanisms are involved. We fed laying hens a 0.5% betaine-supplemented diet for 4 wks to investigate its effect on hepatic lipids metabolism in vivo and confirmed its mechanism via in vitro experiments using embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
0
20
2
Order By: Relevance
“…GR can be activated via both ligand-dependent [ 48 ] and ligand-independent manners [ 49 ]. Previously, we reported CORT-dependent GR activation in the liver of CORT-treated chickens [ 16 , 50 ]. In this study, chickens are not treated with CORT and the plasma CORT level was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…GR can be activated via both ligand-dependent [ 48 ] and ligand-independent manners [ 49 ]. Previously, we reported CORT-dependent GR activation in the liver of CORT-treated chickens [ 16 , 50 ]. In this study, chickens are not treated with CORT and the plasma CORT level was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering the higher percentage of sexually regressed females and lower yield per bird from control fed parents, there are very likely to be positive downstream methylation implications for sexual maturity and productivity from the HiBET diet 51 , 52 . Indeed, other studies have demonstrated that 1-carbon-metabolic essential nutrient diet supplementation can heighten reproductive performance 23 , 46 , 47 . It is plausible that these effects are again due to increased hepatic enzyme activity that has been transmitted via transgenerational mechanisms to the G 1 , resulting in (at least) enhanced reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental betaine potentially caused hypomethylation of the promoter of GR , followed by enhanced expression of GR and GR/ER α interaction (contributed to increase VTGII expression in the liver), which partly supported improved egg production in betaine-supplemented laying hens ( Omer et al, 2018 ). Furthermore, promoter region methylation could be the possible regulatory mechanism underlying altered expression of liver lipid synthesis and transport-related genes in response to betaine supplementation, which supported the synthesis and release of yolk precursor substances in the liver and consequently promoted egg laying performance ( Omer et al, 2020 ).…”
Section: Evidence Of the Impacts Of Epigenetic Processes On Livestockmentioning
confidence: 99%